The Effectiveness of Compassion-Focused Therapy on Emotional Processing in University Students with Depressive Symptoms in Isfahan - Zare, Mohammad Matin; Bakhtiar Nasrabadi, Hasanali (Mental Health and Lifestyle Journal, 2026)
Compassion-Focused Therapy (CFT) can help ameliorate psychological issues by enhancing acceptance and reducing self-criticism. The present study aimed to investigate the effectiveness of Compassion-Focused Therapy on emotional processing in university students exhibiting depressive symptoms in Isfahan. The research methodology employed a quasi-experimental design, specifically a pre-test/post-test design with a control group. The statistical population comprised all university students studying in Isfahan during the second semester of the 2024-2025 academic year. The total sample size consisted of 36 individuals for both the experimental and control groups, who were selected using purposive sampling and subsequently randomly assigned to either the experimental or the control group. Data collection was conducted using the Emotional Processing Scale (EPS) developed by Baker et al. (2010). The Compassion-Focused Therapy intervention was implemented based on Gilbert’s (2009) treatment protocol across eight one-hour sessions. Furthermore, the screening of students for depressive symptoms was performed using the Beck Depression Inventory-II (BDI-II) (1996). Statistical analyses were executed using SPSS version 23 software. The results demonstrated that Compassion-Focused Therapy had an effect on emotional processing variables. Additionally, the therapy significantly influenced the components of emotional processing ( ). The findings revealed that Compassion-Focused Therapy led to the improvement of emotional processing in students with depression ( ). Ultimately, this intervention proved effective in modulating disrupted emotional and interpersonal patterns.